Retrospective analysis of subclavian venous catheterization procedures performed with ultrasound guidance by anesthesiology residents in the intensive care unit - Yalçınkaya, Adem; Kahraman, Abdullah; Kahraman, Cahide; Sezgi, Atakan; Güngördü, Ezgi; Mentes, Oral; Doğanay, Güler Eraslan; Didik, Melek; Ozanbarcı, Azra; Ergil, Jülide (Frontiers in Medicine, 2025)
ObjectivesThe aim of this study was to promote the safe implementation of subclavian catheterization under ultrasound guidance in the intensive care unit, a method associated with relatively low infection rates and enhanced patient comfort. Additionally, this approach seeks to encourage its prioritization by anesthesiology trainees and to increase its active utilization in anesthesiology training programs.Materials and methodsFollowing the approval of the Ethics Committee of Etlik City Hospital, confidence assessments were conducted before and after subclavian catheterization procedures performed under ultrasound guidance by anesthesiology trainees in the anesthesiology intensive care unit between 2023 and 2024. The procedures were then retrospectively analyzed, and complications were documented.ResultsNo major complications were observed in any of the patients undergoing the procedure in the intensive care unit. Retrospective analysis of 40 patients revealed that 23 (57.5%) were male and 17 (42.5%) were female, with a mean age of 73.4 ± 11.3 years. Thrombosis occurred in only one patient (2.5%). Confidence assessments conducted among anesthesiology trainees demonstrated a statistically significant increase in confidence levels following training. None of the patients developed pneumothorax or hemothorax.ConclusionIt was concluded that other catheterization methods (jugular, femoral) are more frequently preferred during anesthesiology residency training. Encouraging trainees to perform subclavian catheterization under ultrasound guidance could be more beneficial in managing critically ill patients during the specialization process.